Дослідження впливу динаміки лінійних двигунів в модулях переміщення упаковок - Якимчук, Микола Володимирович (My University, 2012)
В статті розглядається можливість використання лінійних асинхронних двигунів для виконання операцій лінійних переміщень упаковок з використанням різних конструкцій захоплюючих пристроїв. Представлені математичні моделі для визначення основних кінематичних та динамічних параметрів таких конструкцій. Отримані результати можна використовувати для конструювання модулів переміщення з лінійними двигунами.

The article below shows the possibility of using linear asynchronic engines for linear packaging of various devices. In the article combined the most common designs of exciting devices: vacuum, transmission. There is a mathematical model for determining of basic kinematic and dynamic parameters of such constructions in the article. Equivalence of theoretical results to real verified by the experimental aggregate for the research of linear motor. Optimum modes of operation of linear actuators in lifting mechanisms are depends on the kind of exciting device and method of loading. In the article methods for the analysis of experimental plots of acceleration are developed. These methods are also applied to the harmonic graphs. Presented results can be used to develop modules of movement with linear motors.
Keywords: захоплювальний пристрій; пакувальне обладнання; лінійний двигун; gripping device; packaging equipment; кафедра мехатроніки та пакувальної техніки